Relationships between Social Support and Quality of Life in Schizophrenia Patients - หงษ์กิตติยานนท์, ฐิตวันต์; ทิพย์วงศ์, อารยา (Journal of The Royal Thai Army Nurses, 2018)
This aims were to study correlation and to predict about social support and quality of Life in Schizophrenia Patients .This samples were 400 patients using questionnaires by Muti-stage random Sampling. They were tested for content validity by 3 experts. The data were analyzed using the percentage, means, standard deviations, ,Pearson’s product moment correlation and Stepwise Multiple Regression. Result revealed that : social support at a moderate level ( = 81.87, S.D = 8.03) The social support was positively related to the quality of life schizophrenic patients. (r = .579) Factors significantly predicted quality of life schizophrenic patients were emotional, social support, information, participation at the .01 Predicted quality of life schizophrenia patients (raw scores) were Y⁄ = 52.565+.920x1+ 1.213x5 + .683x3 Results indicate that healthcare team should develop program or activities to provide social support for schizophrenic patients to increase quality of life.